EFFECT OF PRODUCT MARKET MATRIX ON THE PERFORMANCE OF MEDIUM ENTERPRISES IN NORTH CENTRAL, NIGERIA - Garba , Adamu (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2024)
This research work examined the effect of product market matrix on the performance of medium enterprises in North Central, Nigeria. The researcher used primary data source from a sample of three hundred and eighty four (384) respondents obtained by the use of a structured questionnaire. The data collected was analyzed using descriptive statistics such as frequency, simple percentage and the relationship between the variables of the model were tested using multiple linear regression analysis. The hypotheses of the study were tested using the probability value of the regression estimates. The result of the regression analysis indicates that Market penetration strategy's regression coefficient is 0.401 and significant (p0.05).  Product development strategy is -0.059 and negligible (p0.05). A one-unit increase in product development decreases medium firm performance by 0.059 units. A one-unit increase in market development strategy increases medium firm performance by 0.196 units (p0.05). Product diversification approach has a strong coefficient of 0.319. This means a one-unit improvement in product diversification strategy increases medium firm performance by 0.319 units. It was concluded that businesses must consider the region's market conditions, competitive hurdles, and client behaviors to flourish. It was recommended among others that Market Penetration and Product Diversification Strategies are advised for medium enterprises in North Central Nigeria due to their benefits. Expanding market share and targeting existing clients can increase performance. Diversifying products to fulfill client needs can enhance revenue and performance. Firms should use both methods to optimize profits.